EFEKTIFITAS KEBIJAKAN IMPOR PRODUK TERTENTU (PERMENDAG No. 56/M-DAG/PER/12/2008) - . Hasni (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2010)
Permendag 56/M-DAG/PER/12/2008 published in hopes of reducing illegal imports of products circulating in the regulated import of certain products are footwear, electronics, toys, food and beverages, and textiles. Imports of certain products can only be done by companies that have been designated as a Registered Importer (IT) Certain products and through specific ports set by the government. During the year 2009 the realization of the import of certain products has been decreasing over the last 5 years after its imports keeps rising high between 25% -43% per year, this shows that government policy has been to reduce the import of certain products.